Perancangan Prototipe Sistem Pemanggil Perawat Nirkabel menggunakan Keypad dan Transceiver NRF24L01 - Corida, Marselus Setiawan; Pawelloi, A. Irmayani; Zainal, Muhammad (Fakultas Teknik Universitas Muhammadiyah Parepare (FT-UMPAR), 2024)
Hospital health services require effective communication tools between patients and nurses for patient comfort. Along with the development of wireless technology, many nurse call systems have been developed by researchers, application developers, and electronics activists to produce a more effective system and ease of use. The purpose of this study is to design a prototype of a wireless nurse caller system using NRF24L01 communication, and a keypad as a button that can be used by patients in the inpatient room to call patients, as well as an audio system in the nurse's room to receive calls from patients. By using the System Development Life Cycle (SDLC) method, the prototype of the nurse caller system was successfully realized and tested at the range and delay without obstacles and with obstacles. Based on the results of the distance and delay test in the unobstructed area, the caller node device and the call receiving node device can communicate at a distance of <100 meters with an average delay of 70.4 ms. Meanwhile, in the area where there is an obstacle (in the building), it shows the maximum communication ability between devices at a distance of 60 m with a delay of 74 ms and an average delay of 71 ms, Thus this prototype can be applied in hospitals.